A 477‐year dendrohydrological assessment of drought severity for Tsable River, Vancouver Island, British Columbia, Canada. Issue 11 (14th December 2015) - Coulthard, Bethany; Smith, Dan J.
Abstract: Summer streamflow droughts are becoming more severe in many watersheds on Vancouver Island, British Columbia, as a result of climate warming. Small coastal basins that are the primary water source for most communities and essential to Pacific salmon populations have been particularly affected. Because the most extreme naturally occurring droughts are rarely captured within short instrumental records water managers likely underestimate, and are unprepared for, worst‐case scenario low flows. To provide a long‐term perspective on recent droughts on Vancouver Island, we developed a 477‐year long dendrohydrological reconstruction of summer streamflow for Tsable River based on a network of annual tree‐ring width data. A novel aspect of our study is the use of conifer trees that are energy limited by spring snowmelt timing. Explaining 63% of the instrumental streamflow variability, to our knowledge the reconstruction is the longest of its kind in British Columbia. We demonstrate that targeting the summer streamflow component derived from snowmelt is powerful for determining drought‐season discharge in hybrid runoff regimes, and we suggest that this approach may be applied to small watersheds in temperate environments that are not usually conducive to dendrohydrology. Our findings suggest that since 1520, 21 droughts occurred that were more extreme than recent 'severe' events like those in 2003 and 2009. Recent droughts are therefore not anomalous relative to the ~400‐year pre‐instrumental record and should be anticipated within water management strategies. In coming decades, worst‐case scenario natural droughts compounded by land use change and climate change could result in droughts more severe than any since 1520. The influence of the Pacific Decadal Oscillation on instrumental and modelled Tsable River summer streamflow is likely linked to the enhanced role of snowmelt in determining summer discharge during cool phases. Copyright © 2015 John Wiley & Sons, Ltd.